Effects of two different short-term training programs on the physical and technical abilities of adolescent basketball players - Bogdanis, G. C.; Ziagos, V.; Anastasiadis, M.; Maridaki, M. (Journal of Science and Medicine in Sport, 2007)
This study evaluated and compared the effectiveness of two different off-season, short-term basketball training programs on physical and technical abilities of young basketball players. Twenty-seven adolescent basketball players (14.7 ± 0.5 years; Tanner stage: 3.5 ± 0.5) were randomly divided into a specialized basketball training group (SP, n = 10), a mixed basketball plus conditioning training group (MX, n = 10) and a control group (n = 7). Training included five sessions per week (100-120 min each) and was performed for 4 weeks. Maximal oxygen uptake was similarly improved after SP (4.9 ± 1.8%) and MX (4.9 ± 1.4%), but there was no effect on ventilatory threshold. Peak and mean power output measured during the Wingate test were also improved by a similar magnitude after SP (21 ± 5%) and MX (15 ± 6%). Trunk muscle endurance was equally increased (SP: 23 ± 4%, MX: 25 ± 5%), but arms endurance was improved significantly more after MX (50 ± 11%) compared to SP (11 ± 14%, p < 0.05). Performance in four basketball technical skills was similarly increased (by 17-27%) in both groups, with a tendency for greater improvement of the SP groups in the technical skills of shooting and passing. These results indicate that a SP basketball training program, performed exclusively on-court was as effective as a MX training program in terms of aerobic and anaerobic fitness improvement. Furthermore, the decrease of the total on-court training time in the MX group resulted in a tendency for a smaller improvement of basketball technical skills. In conclusion, both SP and MX training are equally effective in order to limit and/or reverse the detraining effects that occur during the off-season in basketball.